2014
DOI: 10.1002/ppap.201400016
|View full text |Cite
|
Sign up to set email alerts
|

Approaches to Quantify Amine Groups in the Presence of Hydroxyl Functional Groups in Plasma Polymerized Thin Films

Abstract: The quantification of primary and secondary amines in plasma polymerized allylamine and plasma copolymers of allylamine/octadiene films was carried out using chemical derivatization followed by X‐ray photoelectron spectroscopy. Data was analyzed using a combination of the peak‐fit‐analysis method (PFA) and the quantitative‐elemental‐analysis method (QEA). The latter method overestimates the secondary amine contribution, since it does not account for the additional reaction of TFAA with OH groups that may be pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 56 publications
2
40
0
7
Order By: Relevance
“…Survey spectra were charge corrected by setting the aliphatic carbon peak to 285 eV. The concentration of surface primary amines was determined using the QEA method described elsewhere …”
Section: Methodsmentioning
confidence: 99%
“…Survey spectra were charge corrected by setting the aliphatic carbon peak to 285 eV. The concentration of surface primary amines was determined using the QEA method described elsewhere …”
Section: Methodsmentioning
confidence: 99%
“…Klages et al [120] and Ruiz et al [121], however, underline that derivatization is not a trivial and easy method, and that in some cases, a distinction between primary, secondary amines or hydroxyl groups is not obvious due to a lack of specificity of the derivatization agents and necessitates calculations. Klages et al even suggest that, due to the presence of imines (randomly generated during plasma polymerization), the derivatization of primary amines on plasma-deposited coatings will always present uncertainties, due to the poor selectivity with respect to imines [120].…”
Section: Use Derivatization When Availablementioning
confidence: 97%
“…Fluorine (F 1s) [121] TFAA also reacts with C-OH [121], >NH [121,127], and amidogroups [127]** 4-(trifluoromethyl)benzaldehyde (TFBA) Fluorine (F 1s) [121] C-OH (alcohol) 286.5 eV [128] trifluoroacetic anhydride (TFAA) Fluorine (F 1s) [24,121,122,126,[129][130][131][132] Epoxyde 287.2 eV [133] trifluoroacetic acid Fluorine (F 1s) [133] Trifluoroacetic acid also reacts with C-OH [133] [125,126,129,131,132,[137][138][139][140] TFE is used with different catalysts such as dicyclohexylcarbodiimide (DCC) [125] and di-tertbutylcarbodiimide (DBC) [129] * The XPS C-N component may include primary, secondary amines, or other moieties, which results in variability of the average BE. ** However, Holländer et al have shown that it is still possible to differentiate alcohols and primary amines on the C 1s lineshape [141].…”
Section: Page 36 Of 52mentioning
confidence: 99%
“…Another important derivatization reagent which has frequently been used for XPS analysis of oxygenated or nitrogenated polymer surfaces is trifluoroacetic anhydride (TFAA), generally supposed to form trifluoroacetate esters with hydroxy groups and trifluoroacetamides with secondary and primary amino groups . The dominant opinion today is that TFAA reacts exclusively with XH moieties, X = O, N; other reaction possibilities of TFAA were mostly neglected (see below, chapter 2.5, for an exception).…”
Section: Chemical Derivatization Analysismentioning
confidence: 99%